2000
DOI: 10.1507/endocrj.47.739
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor-I-Dependent Signal Transduction Pathways Leading to the Induction of Cell Growth and Differentiation of Human Neuroblastoma Cell Line SH-SY5Y. The Roles of MAP Kinase Pathway and PI 3-Kinase Pathway.

Abstract: Abstract.IGF-I regulates cell growth, differentiation, and survival in many cultured nerve cell lines. The present study was undertaken in the human neuroblastoma cell line, SH-SY5Y, to elucidate whether there are differences in the IGF-dependent signal transduction pathways that stimulate proliferation compared to those that induce differentiation.Quiescent SH-SY5Y cells were treated with IGF-I in the presence or absence of PD98059 (an inhibitor of MEK, a MAP kinase kinase) or LY294002 (an inhibitor of PI 3-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 28 publications
6
57
0
3
Order By: Relevance
“…Results from the current study suggest that IGF-I activation of both Insulin-like growth factor-I signaling in neuroblastoma B Kim et al PI 3-K and MAPK pathways is needed for IGF-Imediated neurite outgrowth in N cells. In agreement with our results, Kurihara et al (2000) reported that inhibition of either MAPK or PI 3-K pathways results in decreased neurite outgrowth, while Sarbassov and Peterson (1998) found that PI 3-K is required for the prolonged activation of MAPK in myogenic differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…Results from the current study suggest that IGF-I activation of both Insulin-like growth factor-I signaling in neuroblastoma B Kim et al PI 3-K and MAPK pathways is needed for IGF-Imediated neurite outgrowth in N cells. In agreement with our results, Kurihara et al (2000) reported that inhibition of either MAPK or PI 3-K pathways results in decreased neurite outgrowth, while Sarbassov and Peterson (1998) found that PI 3-K is required for the prolonged activation of MAPK in myogenic differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…Next, we tested candidate growth factors as potential regulators of MAPK pathway activity in progenitor cells. Our attention centered on IGF-1 since it has been shown to both regulate the MAPK cascade and increase the rate of progenitor cell proliferation in the dentate gyrus (Aberg et al, 2000(Aberg et al, , 2003Kurihara et al, 2000). Initially, we examined the expression pattern of IGF-1 in the dentate gyrus.…”
Section: Regulation Of the Mapk Pathway By Insulin-like Growth Factormentioning
confidence: 99%
“…23 The selective PI3-kinase inhibitors wortmannin and LY294002 caused dose- To assess the influence of IGF-1 on MS, SH-SY5Y cells were treated identically to PLM studies and assayed for enzyme activity, measured as the conversion of homocysteine to methionine. As shown in Table 1, IGF-1 increased MS activity to 212% of the basal level.…”
Section: Igf-1 Stimulates Msmentioning
confidence: 99%